PENGARUH KETAHANAN EKONOMI KELUARGA DAN FASILITAS BELAJAR TERHADAP MOTIVASI SISWA SMK YASPEN JAKARTA DI MASA PANDEMI COVID-19 - Iin Suprihatin; Lindiawatie Lindiawatie; Dhona Shahreza (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2022)
The Covid-19 pandemic that hit the entire world in 2020 has caused paralysis of economic activity and changes in the world of education. Teaching and learning activities can only be done in a virtual way that requires adequate facilities and communication technology networks. Meanwhile, on the other hand, economic life has decreased. This study aims to determine the effect of family economic resilience and learning facilities on students' learning motivation during the COVID-19 pandemic. The data collection method was by distributing questionnaires randomly to 30 students in one of the private vocational schools in Jakarta. Data analysis using multiple regression. Based on the hypothesis test, the results of the family economic resilience variable have a negative or no effect on students' learning motivation during the pandemic, but from the regression equation, family economic resilience has an inverse relationship with learning motivation. This means that when the family's economic resilience is low, the motivation to learn is high and vice versa. While learning facilities have a significant effect on learning motivation during a pandemic, and from the regression equation it has a direct relationship with learning motivation. This means that when the learning facilities are adequate, the motivation to learn is also high. Meanwhile, together, the variables of family economic resilience and learning facilities significantly affect students' learning motivation during the covid-19 pandemic